2018
DOI: 10.3390/polym10020226
|View full text |Cite
|
Sign up to set email alerts
|

Woven Fabrics Made of Auxetic Plied Yarns

Abstract: Auxetic plied yarns are specially constructed with two types of single yarns of different sizes and moduli. This paper investigates how to use these types of yarns to produce woven fabrics with auxetic effects. Four-ply auxetic yarns were first incorporated into a series of woven fabrics with different design parameters to study their auxetic behavior and percent open area during extension. Effects of auxetic plied yarn arrangement, single component yarn properties, weft yarn type, and weave structure were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Ng et al produced 6-ply auxetic yarns and reported on their auxetic behaviour as well. However, they compared the NPR among the DHY, the 4-ply and the 6-ply auxetic yarn (Figure 7) and concluded that the 4-ply auxetic yarn has a greater NPR result than the other two auxetic yarns [2]. Compared to the DHY which has a filament helically wrapped around a barely twisted filament and is unstable, the auxetic plied yarn is more robust.…”
Section: Fundamentals Of Auxetic Yarnsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ng et al produced 6-ply auxetic yarns and reported on their auxetic behaviour as well. However, they compared the NPR among the DHY, the 4-ply and the 6-ply auxetic yarn (Figure 7) and concluded that the 4-ply auxetic yarn has a greater NPR result than the other two auxetic yarns [2]. Compared to the DHY which has a filament helically wrapped around a barely twisted filament and is unstable, the auxetic plied yarn is more robust.…”
Section: Fundamentals Of Auxetic Yarnsmentioning
confidence: 99%
“…The behaviour of the material under deformation in this case is dictated by Poisson's ratio, which is one of the fundamental mechanical properties of materials [1]. Poisson's ratio is defined as the ratio of lateral contractile strain to longitudinal tensile strain [2]. Positive value of Poisson's ratio is found in all common materials, which means they contract transversely under uniaxial extension and extend laterally when compressed in one direction [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations